Analysis of language politeness strategies in the film The School for Good and Evil (2022) - Dyah Puteri Indraswari; Nur Utami Sari’at Kurniati; Maulana Taufik (Universitas Pakuan, 2026)
This research is grounded in the importance of understanding language politeness in communication, particularly in fictional contexts such as films that reflect social values. This study aims to identify and analyze politeness strategies in the film The School for Good and Evil (2022), based on Brown and Levinson’s (1987) theory as presented in Cutting and Fordyce (2020), and linked to the characteristics of politeness according to Leech (2014). A qualitative descriptive method was employed, using the non-participant observation technique to collect the data. The findings reveal five types of politeness strategies: on record-baldly, on record-positive politeness, on record-negative politeness, off record, and overlaps. These strategies are influenced by social relationships, power dynamics, and communicative goals. The findings also indicate that politeness not always reflect sincerity, but can be used strategically to influence the interlocutor. Politeness in this film plays a significant role in shaping character dynamics and the storyline.